Detection of Compound Heterozygous of Hb Constant Spring and Hb Q-Thailand by Capillary Electrophoresis and High Performance Liquid Chromatography - Sakorn Pornprasert (2018)
© 2014, Indian Society of Haematology & Transfusion Medicine. A capillary electrophoresis (CE) has proven to be superior to a high performance liquid chromatography (HPLC) in the detection of hemoglobin Constant Spring (Hb CS). Thus the aim of this study was to analyze the efficacy of CE and HPLC for the detection of Hb CS in samples with compound heterozygous of Hb CS and Hb Q-Thailand. Hemoglobin analysis was performed in blood samples of 2 patients with compound heterozygous of Hb CS and Hb Q-Thailand by using HPLC and CE. The HPLC chromatogram and CE electrophoregram of the two techniques were compared. Hb CS was not found on HPLC chromatogram while Hb QA < inf > 2 < /inf > (α < inf > 2 < /inf > < sup > QT < /sup > δ < inf > 2 < /inf > ), a derivative of Hb Q-Thailand, was presented at the retention time of 4.70–4.80 min and it was close to the retention time of Hb CS. On CE electrophoregram, Hb CS was presented at zone 2 (Z2) and it was distinctly separated from Hb QA < inf > 2 < /inf > which was presented at Z1. Therefore, CE was more efficient to the HPLC for diagnosis of compound heterozygous of Hb CS and Hb Q-Thailand.